Lepus americanus Erxleben 1777 - Don E. Wilson; Thomas E. Lacher, Jr; Russell A. Mittermeier (Lynx Edicions, 2016)
46. Snowshoe Hare Lepus americanus French: Lievre dAmérique / German: Schneeschuhhase / Spanish: Liebre americana Other common names: Snowshoe Rabbit, Varying Hare Taxonomy. Lepus americanus Erxleben, 1777, “in America boreeli, ad fretum Hudsonis copiosissimus.” Restricted by E. W. Nelson in 1909 to “Fort Severn,” Ontario, Canada. It is taxonomically distinct from other species of Lepus and does not hybridize with any of them. As taxonomists are still trying to clarify the species differentiation in Lepus, the subspecific taxonomy is not elaborated yet. Recognition of subspecies might not be justified by the fact that variation is clinal and follows climatic gradients. Fifteen subspecies recognized. Subspecies and Distribution. L.a.americanusErxleben,1777—C&ECanada(SENorthwestTerritories,SENunavut,mostAlberta,Saskatchewan,andManitoba,S&SEOntario,Quebec,L.a.,andNewfoundland),alsoinNCUSA(NEMontanaandNorthDakota). L.a.bairdiiHayden,1869—SWCanada(SEBritishColumbiaandSWAlberta)andWCUSA(W&CMontana,Idaho,W&SCWyoming,NE&CUtah,NW&CColorado,andNCNewMexico). L.a.cascadensisNelson,1907—SWCanada(SCBritishColumbia)andNWUSA(SC,C&NCWashington). L.a.columbiensisRhoads,1895—RockyMtsinSWCanada(SEBritishColumbia,WCAlberta),andNWUSA(NEtipofWashington). L.a.dalliMerriam,1900—Alaska(USA)andNWCanada(NWAlberta,NBritishColumbia,YukonexcepttheNtip,S&WNorthwestTerritories). L.a.klamathensisMerriam,1899—WUSA(SWOregonandNCalifornia). L.a.oregonusOrr,1934—WUSA(NE&COregon). L.a.pallidusCowan,1938—SWCanada(WC&CBritishColumbia). L.a.phaeonotusJ.A.Allen,1899—WGreatL.a.RegioninSCCanada(SEtipofSaskatchewan,SManitoba,SWOntario)andNCUSA(NEtipofNorthDakota,Minnesota,NWisconsin,andNMichigan). L.a.pineusDalquest,1942—SWCanada(SCtipofBritishColumbia)andNWUSA(EWashington,NIdaho,NWtipofMontana). L.a.seclususBaker&Hankins,1950—NCUSA(SCtipofMontana,NCtipofWyoming). L.a.struthopusBangs,1898—ECanada(EQuebec,NewBrunswick,NovaScotia,PrinceEdwardI)andNEUSA(Maine). L.a.tahoensisOrr,1933—WUSA(ECCaliforniaandWCNevada). ...